The TolC homologue of Brucella suis is involved in resistance to antimicrobial compounds and virulence - Posadas, D.M. (2007)
Brucella spp., like other pathogens, must cope with the environment of diverse host niches during the infection process. In doing this, pathogens evolved different type of transport systems to help them survive and disseminate within the host. Members of the TolC family have been shown to be involved in the export of chemically diverse molecules ranging from large protein toxins to small toxic compounds. The role of proteins from the TolC family in Brucella and other α-2-proteobacteria has been explored little. The gene encoding the unique member of the TolC family from Brucella suis (BepC) was cloned and expressed in an Escherichia coli mutant disrupted in the gene encoding TolC, which has the peculiarity of being involved in diverse transport functions. BepC fully complemented the resistance to drugs such as chloramphenicol and acriflavine but was incapable of restoring hemolysin secretion in the tolC mutant of & coli. An insertional mutation in the bepC gene strongly affected the resistance phenotype of B. suis to bile salts and toxic chemicals such as ethidium bromide and rhodamine and significantly decreased the resistance to antibiotics such as erythromycin, ampicillin, tetracycline, and norfloxacin. Moreover, the B. suis bepC mutant was attenuated in the mouse model of infection. Taken together, these results suggest that BepC-dependent efflux processes of toxic compounds contribute to B. suis survival inside the host. Copyright © 2007, American Society for Microbiology. All Rights Reserved.